ANALISIS PENGGUNAAN ENERGI LISTRIK GEDUNG LABORATORIUM BIOTEKNOLOGI SERPONG - palaloi, sudirman (Badan Pengkajian dan Penerapan Teknologi, 2008)
This paper is reporting an analysis energy use on Biotechnology Laboratory in Puspiptek Area. Analysis of electrical energy use concern power demand and power factor improvement. Power demand improvement can be done by reducing power purchase close to maximum power that might be happened. It is verybeneficial for reducing fix load cost. Power factor improvement as part of energy saving can reduce losses at distribution line, motor, transformer, reduce installed capacity, and also avoid penalty factor. Optimization of transformer operation can also reduce core and copper winding losses. According to the analysis gave theresult of saving potential is Rp. 218,72 million/year.